PUTUSAN PENJATUHAN PIDANA SEUMUR HIDUP DALAM KASUS PEMBUNUHAN BERENCANA DENGAN TERDAKWA FERDY SAMBO DITINJAU DARI PERSPEKTIF TEORI KEADILAN - Wulandari, Aulia Adelia; Susanti, Rahtami (Collegium Studiosum Journal, 2025)
The premeditated murder case involving the defendant Ferdy Sambo has attracted attention due to its involvement of law enforcement officers and resulting in a life imprisonment sentence. This research aims to analyze the ruling from the perspective of justice theory, particularly according to Aristotelian views. The method used is a juridical-normative approach to the judge's ruling and legal considerations. The findings indicate that the decision reflects retributive justice leaning towards a more rehabilitative and humane approach. However, in distributive and corrective justice, debates arise regarding the proportionality of the punishment, the defendant's position as a former high-ranking police officer, and public expectations of justice. This ruling is legally valid, yet it leaves unresolved moral and ethical questions in its implementation.